Editor Choice: Implementation of the government regulatory Improvement of Colima - Vargas- Hernández, José G.; DÃaz Laureano, Irma Yolanda (Journal of Business Management and Economics, 2017)
The objectiveconcernsdemonstratethe importance ofstudying theimplementation of programsofregulatory reforminthe government of thestate of Colima,is to identifythe degree offulfillment ofthe objectivesin the implementation,the proposed method isthe document review, ethnographyand interviews,asmain conclusionshows thatthisinformationis highly relevantbecause it showsdata fora successfulpublic policy thattranslates into benefitsfor society andthe competitiveness of thestate.